1985
DOI: 10.1002/ajim.4700080303
|View full text |Cite
|
Sign up to set email alerts
|

Safety and health in boatbuilding and repair

Abstract: Boatbuilding is a complex, chemically intensive industry which employs approximately 43,000 workers in the United States, 77% of them in shops with fewer than 20 workers. Boatbuilders and repairers are at high risk of occupational injury from falls, lacerations, low back trauma, repetitive motion, noise, burns, fires, and explosions. Also they are at risk of acute and chronic illness, including dermatitis, toxic hepatitis, peripheral neuropathy, and chronic encephalopathy as a result of their occupational expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Hunting (20) reported that, in a prospective study of union painters using oil-based paints, exposure to solvents was associated with slips and falls. Boat builders are another occupational group exposed to sol vents, and they are known to be at increased risk of fall injury (21). The role of solvent exposure in severe occupational falls is an area needing further study.…”
Section: Discussionmentioning
confidence: 99%
“…Hunting (20) reported that, in a prospective study of union painters using oil-based paints, exposure to solvents was associated with slips and falls. Boat builders are another occupational group exposed to sol vents, and they are known to be at increased risk of fall injury (21). The role of solvent exposure in severe occupational falls is an area needing further study.…”
Section: Discussionmentioning
confidence: 99%
“…Styrene is associated with neurotoxic effects and respiratory effects [Chmielewski and Renke, 1975; Brigham and Landrigan, 1985; Moscato et al, 1987; Kolstad et al, 1995]. Notably, there are recent case reports of obliterative bronchiolitis in England and Taiwan in the fiberglass boat and water tank industries, which share similar exposures with fiberglass windblade manufacture [Chen et al, 2013; Cullinan et al, 2013].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of air pollutants produced by welding processes on the health of laborers, specifically welders, is a major concern of occupational medicine. In addition to work-related injuries, welders often suffer from acute and chronic occupational diseases such as hepatitis, dermatitis, neuropathy, and encephalopathy and are often associated with respiratory conditions such as chronic obstructive pulmonary disease, asthma, chronic bronchitis, and pneumonia after long-term exposure. Welders are also associated with an increased risk for lung cancer, laryngeal cancer, esophageal cancer, and, potentially, leukemia. …”
Section: Introductionmentioning
confidence: 99%